Nivolumab and daratumumab combination regimens for the treatment of relapsed and refractory multiple myeloma: results of a randomized phase I/II clinical trial - Abdallah, Al-Ola; Lesokhin, Alexander; Wrobel, Tomasz; Jamroziak, Krzysztof; Dytfeld, Dominik; Touzeau, Cyrille; Suvannasankha, Attaya; Leleu, Xavier; Silbermann, Rebecca; Khan, Abdullah M.; Kumar, Shaji; Gertz, Morie; et al. (Frontiers in Hematology, 2023)
Purpose. The phase I/II trial CheckMate 039 (NCT01592370) evaluated the safety, tolerability, and efficacy of nivolumab-daratumumab (ND) in patients with relapsed/refractory multiple myeloma (RRMM). Methods. Patients with RRMM were randomized to receive ND with or without pomalidomide-dexamethasone (Pd) in cohort A and ND or D monotherapy in cohort B. The primary endpoint was safety. Secondary endpoints included minimal residual disease (MRD) negativity status, overall response rate (ORR), duration of response, and progression-free survival (PFS). Results. Cohort A (n = 11) was terminated early due to safety concerns observed with immunomodulatory agents and checkpoint inhibitor combinations in other clinical trials. In the small number of patients treated in cohort A, no new safety concerns were observed but patients who received NDPd had numerically more grade 3/4 adverse events (AEs) and serious AEs compared with ND. Grade 3/4 AEs occurring in ≥ 1 patient in the ND group was anemia (3/6 patients); in the NDPd group, these were neutropenia (3/5 patients), upper respiratory tract infection (2/6 patients), and pneumonia (2/6 patients). In cohort B (n = 63), AE rates were similar between ND and D (any-grade: 87.8% vs 95.5%; grade 3/4: 53.7% vs 45.5%). Grade 3/4 AEs occurring in ≥ 1 patient in the ND group were neutropenia (19.5%), anemia (9.8%), thrombocytopenia (9.8%), and bronchitis (7.3%); in the D group these were anemia and pneumonia (both 9.1%). Immune-mediated AEs for ND were consistent with the known safety profile of nivolumab. In cohort A, all patients (5/5) receiving NDPd and 4/6 receiving ND achieved a response. In cohort B, the ORR with ND was numerically higher than D (22/41 [53.7%] vs 9/22 [40.9%]) and both groups had a median PFS of 6.6 months. ND also showed promising MRD negativity results (next-generation sequencing 10-5, 24.0%; next-generation flow 10-5, 22.2%). Conclusion. NDPd demonstrated no new safety signals and encouraging efficacy despite its early termination. ND was well tolerated with a manageable toxicity and few AEs leading to discontinuation, and demonstrated a numerically higher ORR but equivalent PFS compared with D. Any clinical benefits to OS require a longer follow-up.